# Math (transition)

i need some help figuring out this question

2 3/5c - 1/2 > 3/10

3/5x2 - 1/2 > 3/10 x=2

1. 👍 0
2. 👎 0
3. 👁 77

## Similar Questions

1. ### Algebra

I need help in finding the remainder when you divide 5x2 + 4x -40 by x-4.. (5x2 = 5x(2) I also need to know what is the completely factored form of 4x5 - 256x3 (4x5 = 4x(5) & 256x(3) I also need the solutions of the equation 1.5x2

asked by Jay10 on May 26, 2009
2. ### Composition of Functions

1. Find (f·g)(x) where f(x) = 1/x²+3 and g(x) = √x-2. a) (f·g)(x) = 1/x-2 b) (f·g)(x) = 1/√x-2 +3 c) (f·g)(x) = √-2x²-5/x²+3 2. Find (g·f)(x) where f(x) = x²-2 and g(x) = 5x-8. a) (g·f)(x) = 5x²-18 b) (g·f)(x) =

asked by STUDENT on November 9, 2016
3. ### Check a few more CALC questions, please?

I feel pretty good on my answers. Are there any I got wrong? Thank you for the help! 1. If g(x) = tan (5x^2), then g′(x) = * 10x sec2(5x2) sec2(5x2) –10xsec(5x2)tan(5x2) 10sec2(5x2) 7xsec2(5x2) 2. The inflection point of the

asked by Samantha on December 19, 2013
4. ### Math help please check

Add or Subtract for #3-4 3. (2x2 + 6x + 1) + (–7x2 + 2x – 3) 5x2 – 4x – 2 –5x2 + 8x – 2 5x2 – 8x + 2 –9x2 – 8x + 2 4. (3x2 – 7x – 4) – (6x2 – 6x + 1) –3x2 – x –5 –3x2 –13x + 5 9x2 – x + 5 3x2

asked by Delilah on May 6, 2013
5. ### algebra

Given f(x) = 5x2 – 3x + 1, find f(–2). so would this be 5(-2*-2) -3(-2)+1 answer being 15 not correct (I assume looking at your substitution that the first term is 5x^2 or 5x²) f(x) = 5x^2 – 3x + 1 f(-2) = 5(-2)^2 - 3(-2) +

asked by confused on May 24, 2007
6. ### precalculus

Are my answers correct if not which are right? Find the second difference for the sequence. 7, 6, 7, 10, 15, 22, …. 1 2 3 5 answer:a Find first differences for the sequence in order from a1 to a5. Determine whether or not the

asked by sally on December 14, 2016
7. ### precalculus

can you check my answers? Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) 7 + 13 + 19 + …+[6(k - 1) + 1] + (6k + 1) + [6(k + 1) + 1] 8 + 14 + 20 + …+[7(k - 1) + 1] + (7k + 1) 7 + 13 + 19 + …+(6k + 1) 7 + 13 +

asked by Anonymous on December 14, 2016
8. ### can you check my answers precalculus

can you check my answers? Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) 7 + 13 + 19 + …+[6(k - 1) + 1] + (6k + 1) + [6(k + 1) + 1] 8 + 14 + 20 + …+[7(k - 1) + 1] + (7k + 1) 7 + 13 + 19 + …+(6k + 1) 7 + 13 +

asked by Anonymous on December 14, 2016